The Asia villa guide - Galea, Hilary;Peters, Ed (Singapore : Insight Guides in Asia)
The Asia Villa Guide is laid out by country and destination. Each villa is in a collection and has been given a rating to help you compare.
Indonesia -- Sri Lanka -- Thailand
Includes index.
Keywords: TOURISM -- ASIA